PROGRAM PEMBELAJARAN FONOLOGIS BERBASIS WEB DENGAN MEDIA LEXIROOM UNTUK MENINGKATKAN KESADARAN FONOLOGIS PADA ANAK DISLEKSIA - Tita Rosita, - (2022)
Children with dyslexia have adequate cognitive abilities but show considerable difficulty in learning to read so that they are less accurate in spelling and pronouncing words. Phonological deficit is the main cause of reading disorders in dyslexic children, so developing competence in phonological awareness is important because it will increase children's sensitivity to the structure of a word in language. Therefore, the purpose of this study was to develop a set of learning media for dyslexic children to increase phonological awareness in the aspects of syllable awareness, segmenting words into sounds, and manipulating sounds. This research uses a research and development approach. The research sample is a sixth grade elementary school student with dyslexia because the research design is a single subject. Based on the results of the validation of material experts and media experts that LexiRoom as a web-based learning media is feasible to use. The phonological learning program includes three stages, namely program planning, program implementation, and program evaluation and follow-up. The results of the implementation and evaluation of LexiRoom media were able to significantly increase the phonological awareness of dyslexic children in the aspect of syllable awareness, segmenting words into sounds, and manipulating sounds. In addition, the results of the overlap percentage test show the effect of the intervention on the target behavior. Keywords: Dyslexia, Phonological Awareness, LexiRoom Media.